2022
DOI: 10.1186/s12888-022-03860-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence and interaction of resting state functional magnetic resonance and tryptophan hydroxylase-2 methylation on short-term antidepressant drug response

Abstract: Background Most antidepressants have been developed on the basis of the monoamine deficiency hypothesis of depression, in which neuronal serotonin (5-HT) plays a key role. 5-HT biosynthesis is regulated by the rate-limiting enzyme tryptophan hydroxylase-2 (TPH2). TPH2 methylation is correlated with antidepressant effects. Resting-state functional MRI (rs-fMRI) is applied for detecting abnormal brain functional activity in patients with different antidepressant effects. We will investigate the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 71 publications
1
7
0
Order By: Relevance
“…The promoter region of the TPH2 gene contains several scattered CpG sites rather than CpG islands (Chen GL & Miller GM, 2012). Studies have demonstrated that regulatory polymorphisms of TPH2 may differentially in uence the response to environmental factors, presumably due to their differential roles in gene expression regulation (Shen T et al, 2020;Tan T et al, 2022). Similarly, our ndings suggested that the onset and development of OCD may be regulated by DNA methylation at different CpG sites of the TPH2 gene.…”
supporting
confidence: 60%
“…The promoter region of the TPH2 gene contains several scattered CpG sites rather than CpG islands (Chen GL & Miller GM, 2012). Studies have demonstrated that regulatory polymorphisms of TPH2 may differentially in uence the response to environmental factors, presumably due to their differential roles in gene expression regulation (Shen T et al, 2020;Tan T et al, 2022). Similarly, our ndings suggested that the onset and development of OCD may be regulated by DNA methylation at different CpG sites of the TPH2 gene.…”
supporting
confidence: 60%
“…An ADHD-specific relation between DNA methylation and reaction time variability in a motivational Go/NogoTask has been reported before [ 13 ], supporting the influence of DNA methylation on both, variability and impulsivity. DNA methylation has been linked to personality traits/endophenotypes such as aggression [ 60 ], and the ability to recognize mental states [ 38 ] as well as in the context of affective disorders [ 12 , 61 ] to rs-fMRI-related PFC activity [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…SLC6A4 methylation percentages were estimated at four CpG sites (Table S2) that were previously linked to clinical phenotypes, including depressive symptoms [ 7 , 16 , 26 , 46 ], early-life adversities [ 7 ], recent environmental stress [ 15 ], antidepressant treatment outcome [ 20 , 21 ] and panic disorder [ 16 ]. TPH2 methylation was estimated at 6 CpG sites (Table S2) based on previous studies showing an association with gene expression ( 13 , 26 , 28 ), early life stress, depressive symptoms, antidepressant treatment outcome [ 23 , 24 , 47 ] and attention deficit hyperactivity disorder [ 48 ].…”
Section: Methodsmentioning
confidence: 99%
“…More recently, methylation of TPH2 gene has also been suggested as a biomarker for vulnerability to depression and antidepressant treatment outcome [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%